SISTEM PEMUNGUTAN BEA BALIK NAMA KENDARAAN BERMOTOR PADA PROVINSI KALIMANTAN BARAT - Febriati (Jurnal Akuntansi, Auditing dan Investasi, 2021)
The problem in this research is about how the transfer of motorized vehicle ownership fee collection system in West Kalimantan Province, how the effectiveness of collecting Transfer of Motor Vehicle Title Fee in West Kalimantan Province and the factors that influence the collection system of Transfer of Motor Vehicle Title Fee in West Kalimantan Province. The purpose of this study was to determine the system for collecting Transfer of Motor Vehicle Title Fee in West Kalimantan Province, to determine the effectiveness of collecting Transfer of Motor Vehicle Title Fee in West Kalimantan Province and to determine the factors that mediate the collection of Transfer of Motor Vehicle Title Fee in West Kalimantan Province. The method used in this research is descriptive method, which is to identify the collection system for transferring motor vehicle ownership fees in West Kalimantan Province. The analytical tools used in this research are flowchart analysis, regional tax effectiveness test and questionnaire results. The results of the analysis that have been carried out show that it can be seen that in implementing the system for collecting transfer fees for motor vehicles in West Kalimantan Province, the system is adequate, the Regional Financial and Revenue Management Agency of West Kalimantan Province has implemented the principles of internal control effectively, and the average percentage of the effectiveness of the Transfer of Motor Vehicle Title Fee from 2014 to 2016 is 95%, which means that the collection of Transfer of Motor Vehicle Title Fee carried out by tax collectors in the Regional Government of West Kalimantan Province from 2014 to 2016 has been effective. and from the results of filling in the questionnaire, it appears that there are factors that influence the collection system for transfer of motor vehicle ownership fees in West Kalimantan Province. Keywords: Collection system, Effectiveness, Transfer of Vehicle Name Fees, BPKPD